Let f(x)=4x-1 and g(x)=2x^2+3. Perform each function operations and then find the domain.1. (f+g)(x)   2. (f-g)(x)   3. (g-f)(x)   4. (f times g)(x)    5. f/g(x)   6. g/f(x)

Answers

Answer 1
Answer:

The domain of a function is the set of input values, the function can take.

The values of the composite functions are:

\mathbf{(f + g)(x) = 2x^2 + 4x +2}

\mathbf{(f - g)(x) = -2x^2 + 4x - 4}

\mathbf{(g - f)(x) = 2x^2 - 4x + 4}

\mathbf{(f * g)(x) = 8x^3 - 2x^2 -12x + 4}

\mathbf{(f / g)(x) = ((4x - 1 ))/((2x^2 - 3))}

\mathbf{(g / f)(x) = (2x^2 - 3)/(4x - 1 )}

The functions are given as:

\mathbf{f(x) = 4x - 1}

\mathbf{g(x) = 2x^2 + 3}

\mathbf{(1)\ (f + g)(x)}

This is calculated as:

\mathbf{(f + g)(x) = f(x)+ g(x)}

So, we have:

\mathbf{(f + g)(x) = 4x - 1 + 2x^2 + 3}

Collect like terms

\mathbf{(f + g)(x) = 2x^2 + 4x - 1 + 3}

\mathbf{(f + g)(x) = 2x^2 + 4x +2}

There is no restriction on the value of x.

So, the domain is: \mathbf{(-\infty,\infty)}

\mathbf{(2)\ (f - g)(x)}

This is calculated as:

\mathbf{(f - g)(x) = f(x) - g(x)}

So, we have:

\mathbf{(f - g)(x) = 4x - 1 - 2x^2 - 3}

Collect like terms

\mathbf{(f - g)(x) = -2x^2 + 4x - 1 - 3}

\mathbf{(f - g)(x) = -2x^2 + 4x - 4}

There is no restriction on the value of x.

So, the domain is: \mathbf{(-\infty,\infty)}

\mathbf{(3)\ (g - f)(x)}

This is calculated as:

\mathbf{(g - f)(x) = -(f - g)(x) }

So, we have:

\mathbf{(g - f)(x) = 2x^2 - 4x + 4}

There is no restriction on the value of x.

So, the domain is: \mathbf{(-\infty,\infty)}

\mathbf{(4)\ (f * g)(x)}

This is calculated as:

\mathbf{(f * g)(x) = f(x) * g(x)}

So, we have:

\mathbf{(f * g)(x) = (4x - 1 )* (2x^2 - 3)}

\mathbf{(f * g)(x) = 8x^3 - 2x^2 -12x + 4}

There is no restriction on the value of x.

So, the domain is: \mathbf{(-\infty,\infty)}

\mathbf{(5)\ (f /g)(x)}

This is calculated as:

\mathbf{(f /g)(x) = (f(x) )/(g(x))}

So, we have:

\mathbf{(f / g)(x) = ((4x - 1 ))/((2x^2 - 3))}

There are restrictions to the value of x.

So, the domain is: \mathbf{(-\infty,-\sqrt{(3)/(2)} ) \ u\ ( -\sqrt{(3)/(2)},\sqrt{(3)/(2)}})\ u\ (\sqrt{(3)/(2)},\ \infty)}

\mathbf{(6)\ (g /f)(x)}

This is calculated as:

\mathbf{(g /f)(x) =1 / (f(x) )/(g(x))}

So, we have:

\mathbf{(g / f)(x) = (2x^2 - 3)/(4x - 1 )}

There are restrictions to the value of x.

So, the domain is: \mathbf{(-\infty, (1)/(4))\ u\ ((1)/(4),\infty)}

Read more about domain at:

brainly.com/question/21853810

Answer 2
Answer: f(x) = 4x - 1
g(x) = 2x² + 3

1. (f + g)(x) = (4x - 1) + (2x² + 3)
    (f + g)(x) = 2x² + 4x + (-1 + 3)
    (f + g)(x) = 2x² + 4x + 2
    Domain: {x| -∞ < x < ∞}, (-∞, ∞)

2. (f - g)(x) = (4x + 1) - (2x² + 3)
    (f - g)(x) = 4x + 1 - 2x² - 3
    (f - g)(x) = -2x² + 4x + 1 - 3
    (f - g)(x) = -2x² + 4x - 2
    Domain: {x|-∞ < x < ∞}, (-∞, ∞)
3. (g - f)(x) = (2x² + 3) - (4x - 1)
    (g - f)(x) = 2x² + 3 - 4x + 1
    (g - f)(x) = 2x² - 4x + 3 + 1
    (g - f)(x) = 2x² - 4x + 4
    Domain: {x| -∞ < x < ∞}, (-∞, ∞)

4. (f · g)(x) = (4x + 1)(2x² + 3)
    (f · g)(x) = 4x(2x² + 3) + 1(2x² + 3)
    (f · g)(x) = 4x(2x²) + 4x(3) + 1(2x²) + 1(3)
    (f · g)(x) = 8x³ + 12x + 2x² + 3
    (f · g)(x) = 8x³ + 2x² + 12x + 3
    Domain: {x| -∞ < x < ∞}, (-∞, ∞)

5. ((f)/(g))(x) = (4x - 1)/(2x^(2) + 3)
    Domain: 2x² + 3 ≠ 0
                         - 3  - 3
                        2x² ≠ 0
                         2      2
                          x² ≠ 0
                           x ≠ 0
                  (-∞, 0) ∨ (0, ∞)

6. ((g)/(f))(x) = (2x^(2) + 3)/(4x - 1)
    Domain: 4x - 1 ≠ 0
                      + 1 + 1
                        4x ≠ 0
                         4     4
                         x ≠ 0
                (-∞, 0) ∨ (0, ∞)

Related Questions

Solve for x. 10x^2=29x-21 does anyone know this
16 is what percent of 64
Your school raised 125% of its fundraising goal.The School raised $6750.What was the goal?
Is -4 a real number, rational, irrational, integer, whole or a natural number?
Determine the vertex form of g(x) = x2 + 2x – 1. Which graph represents g(x)? On a coordinate plane, a parabola opens up. It goes through (negative 2, 3), has a vertex at (negative 1, 2), and goes through (0, 3). On a coordinate plane, a parabola opens up. It goes through (negative 1, 2), has a vertex at (1, negative 2), and goes through (3, 2). On a coordinate plane, a parabola opens up. It goes through (0, 3), has a vertex at (1, 2), and goes through (2, 3). On a coordinate plane, a parabola opens up. It goes through (negative 3, 2), has a vertex at (negative 1, negative 2), and goes through (1, 2).

How do I evaluate -7 5/6 + (-7 1/4)

Answers